Bright's passage [large type]: a novel - Ritter, Josh (Thorndike Press large print basic series., 2012)
Newly returned to West Virginia from the First World War, Henry Bright is griefstruck by the death of his young wife and unsure of how to care for their infant son. With the only home he's ever known destroyed, Bright's hopes for safety rest with the angel who's followed him from the trenches of France and who now promises to protect him and his son. Together they make their way through a ravaged landscape toward an uncertain salvation.